Huganbuzure Granule Attenuates Concanavalin-A-Induced Immune Liver Injury in Mice via Regulating the Balance of Th1/Th2/Th17/Treg Cells and Inhibiting Apoptosis. (8th September 2021) - Wang, Mengheng; Yin, Hailong; Xia, Yu; Tu, Yijun; Zou, Xinshuang; Song, Wanci; Luo, Laichun; Wu, Hezhen; Yang, Yanfang; Zan, Junfeng; Liu, Yanwen; Dan, Hanxiong; et al.
Abstract : In Uygur medicine, Huganbuzure granule (HBG) is one of the classical prescriptions for liver protection. However, its role in immune liver injury remains unknown. This study evaluates the effect of HBG on concanavalin-A- (ConA-) induced immune liver injury and investigates its protective underlying mechanism. BALB/c mice were randomly divided into five groups ( n = 24 mice per group): control, ConA, 1.6 g/kg HBG + ConA, 3.2 g/kg HBG + ConA, and 6 mg/kg prednisolone + ConA. HBG was intragastrically administrated once daily for ten consecutive days, prior to ConA (20 mg/kg) injection. The levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin (TBIL), superoxide dismutase (SOD), and malondialdehyde (MDA) in mouse serum were measured after ConA injection. Moreover, liver-related mRNA levels were evaluated by qPCR. The detection of liver-related proteins was assessed by immunohistochemistry and western blot analysis. Compared with the ConA group, HBG reduced the mRNA expression of IL-17A and IFN- γ and the protein expression of T-bet and ROR- γ t. In addition, HBG increased the mRNA expression of IL-4 and TGF- β and protein expression of GATA3 and Foxp3, indicating that HBG regulated the balance of Th1/Th2 and Th17/Treg. Furthermore, HBG alleviated immune liver injury by reducing oxidative stress, inhibiting apoptosis, and decreasing the expression of p-JNK, p-ERK, p-p38, p-JAK1, p-STAT1, p-STAT3, and IRF1. Our data suggested that HBG attenuated ConA-induced immune liver injury by regulating the immune balance and inhibiting JAK1/STATs/IRF1 signaling, thereby reducing apoptosis induced by JNK activation. The findings indicate that HBG may be a promising drug for immune liver injury.